2022
DOI: 10.1002/adma.202200401
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Cycling Sulfide‐Based All‐Solid‐State Batteries Enabled by Electrochemo‐Mechanically Stable Electrodes

Abstract: The anode plays a critical role relating to the energy density in all‐solid‐state lithium batteries (ASLBs). Silicon (Si) and lithium (Li) metal are two of the most attractive anodes because of their ultrahigh theoretical capacities. However, most investigations focus on Li metal, leaving the great potential of Si underrated. This work investigates the stability, processability, and cost of Si anodes in ASLBs and compares them with Li metal. Moreover, single‐crystal LiNi0.8Mn0.1Co0.1O2 is stabilized with lithi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 48 publications
3
102
0
Order By: Relevance
“…If the weight of all inactive materials (e.g., SE, and current collectors) is considered realistically, the specific energy is estimated to be less than 50 Wh kg –1 . Cao et al reported sheet-type Si|NCM SSB cells with a material-level specific energy of 285 Wh kg –1 through sandwiching a silicon anode, a thin sulfide SE membrane, and an interface modified NCM811 cathode …”
Section: Full Cells With Silicon Anodesmentioning
confidence: 99%
See 1 more Smart Citation
“…If the weight of all inactive materials (e.g., SE, and current collectors) is considered realistically, the specific energy is estimated to be less than 50 Wh kg –1 . Cao et al reported sheet-type Si|NCM SSB cells with a material-level specific energy of 285 Wh kg –1 through sandwiching a silicon anode, a thin sulfide SE membrane, and an interface modified NCM811 cathode …”
Section: Full Cells With Silicon Anodesmentioning
confidence: 99%
“…(e) Capacity retention of SSB cells with silicon anodes as a function of cycling number. Data points in (d) and (e) were taken from refs , , , , and .…”
Section: Full Cells With Silicon Anodesmentioning
confidence: 99%
“…[149] Recent studies demonstrated notable progress in Si-based SSEs-LIBs adopting gel-polymer electrolytes, [150] garnet-type [151] or sulfide solid electrolytes. [139,152] Surprisingly, with improved ionic conductivity of electrolyte and Si-SSE interfacial contact, stable full cell cycle performances with 99.9 wt% Coulombic efficiency could be achieved even at high current density (5 mA cm −2 ). [139] This implies that Si-based particles can be seriously regarded as an anode choice alternative to Li metal in solid state batteries.…”
Section: Outlook In Solid-state Batteriesmentioning
confidence: 99%
“…Recent studies have shown that solid-state full batteries using silicon anodes, sulde solid-state electrolytes, and NCM811 cathodes have better cycling performance than lithium metal, which undoubtedly advances the commercialization of silicon anodes. 130,131 In brief, silicon anodes emerge as the most promising anodes for solid-state batteries due to their low cost, ease of scaling up, and high safety. Silicon anodes also exhibit enhanced compatibility with sulde solid-state electrolytes than lithium metal.…”
Section: Discussionmentioning
confidence: 99%